KEPRAKTISAN MODUL BERBASIS ANDROID TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SMA - Hatta Gani; Yudi Firmanul Arifin; Muhammad Zaini (Journal of Banua Science Education, 2022)
This development research aims to describe an Android-based module on the critical thinking skills of high school/vocational high school students. The stages of development include self-evaluation, expert test, individual test, small group test, and field test. The research subjects were 5 students for the re-sponse test and 3 observers for the implementation test of the Android-based module on the critical thinking skills of high school/vocational high school students. The type of data is descriptive data, us-ing a module implementation instrument and student responses are used for the practicality of the con-tent and the practicality of expectations. Technical data analysis was carried out in accordance with the objectives of the research which included the practicality of the module. The data calculation is done by calculating the total score for each aspect tested and then dividing the total score so that a percentage is obtained that shows the practicality of the Android-based module. The results showed that the Android-based module that had been developed was stated to be very practical based on the individual module test with an average of 90,23%. Android-based modules are declared practical be-cause the results of student responses with an average value of 92,65% with very good criteria, the re-sults of implementing the module with an average of 92,20% with criteria strongly agree. Based on this, the Android-based module developed is very practical to use and makes it easier for students to learn.Keywords: Practicality, android-based module, critical thinking ability.ABSTRAKPenelitian pengembangan ini bertujuan mendeskripsikan modul berbasis android terhadap kemampuan berpikir kritis siswa SMA Tahap-tahap pengembangan meliputi evaluasi diri, uji pakar, uji perorangan, uji kelompok kecil, dan uji lapangan. Subjek penelitian adalah 5 siswa untuk uji respon dan 3 observer untuk uji keterlaksanaan modul berbasis android terhadap kemampuan berpikir kritis siswa SMA. Jenis data yaitu data deskriptif, menggunakan instrument keterlaksanaan modul dan respon siswa digunakan untuk kepraktisan isi dan kepraktisan harapan. Teknis analisis data dilakukan sesuai dengan tujuan dari penelitian yang meliputi kepraktisan modul. Perhitungan data dilakukan dengan cara menghitung jumlah skor tiap aspek yang diuji kemudian dibagi jumlah skor total sehingga didapatkanlah persentase yang menunjukan kepraktisan modul berbasis android. Hasil penelitian menunjukan modul berbasis android yang telah dikembangkan dinyatakan sangat praktis berdasarkan uji perorangan modul dengan rata-rata 90,23%. Modul berbasis android dinyatakan praktis karena hasil respon siswa dengan rata-rata nilai 92,65% dengan kriteria sangat baik, hasil keterlaksanaan modul dengan rata-rata 92,20% dengan kriteria sangat setuju. Berdasarkan hal tersebut modul berbasis android yang dikembangkan sangat praktis digunakan dan memudahkan siswa dalam pembelajaran.Kata kunci: Kepraktisan, modul berbasis android, kemampuan berpikir kritis.